Linguistic Strategies and Purchase Intention: Platform and Cultural Effects - Hasyim, Fuad; Ash-shiddiqi, Ali Mahmud (Golden Ratio of Mapping Idea and Literature Format, 2026)
This scoping review article maps how linguistic features influence consumer purchase intention across digital marketing platforms and cultural contexts. Following the PRISMA-SCR framework, it reviewed 19 empirical studies (2015- June 2025) from major academic databases to examine how language features influence consumer behavior in online shopping, live-stream commerce, social media, and e-commerce settings, with cultural perspectives drawn from Japan, Indonesia, China, and other contexts. Key findings indicate that linguistic strategies (tone, style, persuasive appeals, social presence, and cultural congruence) play an important role in enhancing trust, arousal, brand awareness, and purchase intention. The effectiveness of these strategies varies by platform and culture. Conversational language works best in interactive, collectivist contexts, while clarity and authenticity are favored in text-heavy, individualist settings. It also identifies gaps related to platform diversity, cross-cultural comparisons, and theoretical integration, providing a roadmap for future research and culturally responsive marketing strategies.